Identifikasi Permasalahan Mahasiswa Evaluasi Semester Program Akademik dan Vokasi di Institut Teknologi Sepuluh Nopember Surabaya - Yuli Purwanto; Setiawan; Sunawi; Fatkhul Iman Nurdjati; Siti Machmudah (Direktorat Riset dan Pengabdian Kepada Masyarakat, 2024)
This study investigates the issues faced by students with Dispensation, ProbationSemester Promotion, and Non-Promotion statuses based on evaluations from the2021 Even Semester to the 2024 Odd Semester at Institut Teknologi SepuluhNopember, Surabaya. Using a quantitative descriptive approach, the researchexamines problems in semester evaluations. The population consists of 422 activestudents, with a sample of 252 students selected through Proportioned StratifiedRandom Sampling. Data was collected via questionnaires and interviews.Analysis employed the Guidance and Counseling Problem Checklist (DCM) inHigher Education, covering 11 topics through 56 Likert-scale statements.Problems were ranked based on Respondent Achievement Level (TCR)percentages. Findings reveal that the most significant issue is in the